2020
DOI: 10.1017/s0266078420000073
|View full text |Cite
|
Sign up to set email alerts
|

A cheeky investigation: Tracking the semantic change of cheeky from monkeys to wines

Abstract: The present study focuses on the word cheeky which, in the past few decades, has taken on a new meaning of ‘mildly illicit’ in addition to, and partly overtaking, its original meaning of ‘impudent’. We examine how this semantic change is spreading in different age groups and in different parts of the English-speaking world. As we demonstrate, the newer meaning of cheeky is associated with younger speakers, so we examine whether this correlates with different age groups’ understanding of the new form. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Kiesling 2004;Bucholtz 2009) to morphosyntax (Moore & Podesva 2009), to phonetics and phonology (Foulkes & Doherty 2006;Eckert & Labov 2017). However, the study of semantic meaning in sociolinguistics has been somewhat neglected (although, see Robinson 2010aRobinson , 2010bRobinson , 2012aRobinson , 2012bRobinson , 2014Beal & Burbano-Elizondo 2012;Bailey & Durham 2021;Sandow 2023aSandow , 2023b; for discussion see Durkin 2012;Robinson 2012a;Sandow 2021). This article seeks to redress the limited, but growing, body of literature on the socially mediated trajectory of semantic change in the context of social meaning by exploring the polysemous adjective wicked.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kiesling 2004;Bucholtz 2009) to morphosyntax (Moore & Podesva 2009), to phonetics and phonology (Foulkes & Doherty 2006;Eckert & Labov 2017). However, the study of semantic meaning in sociolinguistics has been somewhat neglected (although, see Robinson 2010aRobinson , 2010bRobinson , 2012aRobinson , 2012bRobinson , 2014Beal & Burbano-Elizondo 2012;Bailey & Durham 2021;Sandow 2023aSandow , 2023b; for discussion see Durkin 2012;Robinson 2012a;Sandow 2021). This article seeks to redress the limited, but growing, body of literature on the socially mediated trajectory of semantic change in the context of social meaning by exploring the polysemous adjective wicked.…”
Section: Introductionmentioning
confidence: 99%
“…For example, using elicited data, Robinson (2012a) found the polysemous adjective gay to be undergoing change in apparent-time, with males leading the change from 'happy' towards the senses 'homosexual' and 'lame'. Bailey & Durham (2021) used acceptability judgements to trace the development of the sense cheeky 'mildly illicit', with younger speakers in Britain leading this shift from cheeky 'impudent' towards greater acceptance of the innovative variant. Such studies have demonstrated the structured heterogeneity of semantic change.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, public opinion and public opinion supervision under the new media environment show new features, which not only bring convenience to public opinion expression but also bring difficulties and problems to public opinion regulation and guidance [5]. Therefore, it is necessary to formulate and implement the public relations regulation strategy to adapt to the new media environment [6].…”
Section: Introductionmentioning
confidence: 99%